Phonological Codes Are Automatically Activated During Reading: Evidence From an Eye Movement Priming Paradigm - Rayner, Keith; Sereno, Sara C.; Lesch, Mary F.; Pollatsek, Alexander (Psychological Science, 1995)
Subjects read sentences containing target words that were homophones (words with a single pronunciation but different spellings) while their eye movements were recorded A prime word was presented briefly at the onset of fixation on the target region The prime for a given target (e g, beach) was either identical to the target (beach), a phonologically similar word (the homophone beech), a visually similar nonhomophone (bench), or a dissimilar word (noise) Phonological priming effects were assessed by comparing fixation times on the target when it was preceded by the homophone versus the visually similar word Results suggest that phonological codes are automatically activated during eye fixations in reading